An approach to high-throughput X-ray diffraction analysis of combinatorial polycrystalline thin film libraries - Roncallo, S.; Karimi, O.; Rogers, Keith; Lane, David W.; Ansari, S. A. (Blackwell Publishing Ltd, 2009)
With the demand for higher rates of discovery in the materials field, characterization techniques that are capable of rapidly and reliably surveying the characteristics of large numbers of samples are essential. A chemical combinatorial approach using thin films can provide detailed phase diagrams without the need to produce multiple, individual samples. This is achieved with compositional gradients forming high-density libraries. Conventional raster scanning of chemical or structural probes is subsequently used to interrogate the libraries. A new, alternative approach to raster scanning is introduced to provide a method of high-throughput data collection and analysis using an X-ray diffraction probe. Libraries are interrogated with an extended X-ray source and the scattering data collected using an area detector. A simple technique of 'partitioning' this scattering distribution enables determination of information comparable to conventional raster scanned results but in a dramatically reduced collection time. The technique has been tested using synthetic X-ray scattering distributions and those obtained from contrived samples. In all cases, the partitioning algorithm is shown to be robust and to provide reliable data; discrimination along the library principal axis is shown to be similar to 500 mm and the lattice parameter resolution to be similar to 10(-3) A angstrom mm(-1). The limitations of the technique are discussed and future potential applications described.